Placemaking for Silk Road in Iran: Process and strategies - Mahasti, Payam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Cities, during their lives are facing various urban challenges including threatening economic growth. The manifestation of those challenges is evident in urban spaces and places. In view of that, Iranian cities have been experiencing difficulties in adopting with economic shift from trading to oil industry economy. Such transferal economy has had its impact on Iranian urban places. Although there are many urban spaces in contemporary Iranian cities, there are very few urban places among them. The traditional Iranian cities, however, have had valuable examples of urban places, which especially developed along the main trading routs. Therefore, the aim of this study is to explore and rediscover the quality of successful remained urban places along the renowned trading route of Silk Road in Iran. The main aim of this research is to find out the appropriate approach or method of creating a successful urban public space in Silk Road cities. In this way, two principal objectives to this main purport were formulated, which includes, finding out what are the general and specific characteristics of urban public space for Silk Road cities, and secondly; to define particular approaches for placemaking in the creation of successful places in Silk Road cities. In correlation with the main objectives of this research, two independent or major research question are unfold: What should be the strategies for Place Making? How could Place Making improve the quality of UPS in SRCS in Iran? The research has been started with theoretical investigation about place and placemaking. Definitions and main concerns in line with the subject have been explained and understood. Consequently, the main criteria of placemaking have been investigated and the framework of analysis methodology has been discussed. The result of this investigation is the hierarchy and weight of each assessment that make a place successful. To achieve the weight of assessments the DELPHI technique and SAW method has been used. The site survey has been started with documentary survey about Silk Road cities and settlements in Iran. Through documentary research, the main Silk Road routes and their cities have been introduced. This part includes general information about geographical location, climate, economy and population for each city. The second part of site survey is for distinguishing Silk Road urban places in cities. Through this survey, totally 650 places in 17 cities have been listed. To set the limitation for the survey, an eliminated method for selecting places has been used and finally twelve places from three cities have been chosen. In this method first places which are out of cities have been eliminated. Then places that are not in the urban form have been eliminated. Finally places that are in the historic quarters have been remained. There are totally 12 places in three cities. In analysis part, twelve places have been surveyed and analyzed due to the assessments that were found in theoretical investigations. The analysis focused on reflecting the influence of placemaking assessments on the quality of places in Silk Road cities in Iran. The dissertation concludes that “Street life”, “Social network” and “Pedestrian activity” have more influences to make the Silk Road Places successful. Also it concludes that activities like “Trade” have a strong relation with successfulness of places, in a way that all three “Bazaars” between cases got the highest rank in the list of successful places. The other finding in this research is the importance or the scale of city has less influence for making successful places. Keywords: Silk Road, Place, Placemaking, Iran, SAW methodology. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Kentler, yaşam süreleri boyunca, ekonomik gelişmenin tehtid altında kalması da dahil pek çok kentsel sorunla mücadele etmek durumunda kalırlar. Bu mücadelelerin göstergesi kentsel mekanlarda ve yerlerde belirgindir. Bu bakış açısıyla, İran kentleri, ticaretten endüstri ekonomisine geçişe adapte olmada zoluklar yaşamaktadır. Bu ekonomik geçiş, İran kentsel alanları üzerinde de etkisini göstermektedir. Güncel İran kentlerinde pek çok kentsel alan bulunmasına rağmen, bunların içinde pek az sayıda kentsel mekan vardır. Oysa geleneksel İran kentlerinde, özellikle ticaret yolları boyunca pek çok değerli kentsel mekan örneğine rastlanmaktadır. Bundan dolayı, bu araştırmanın amacı, İran’daki ünlü İpek Yolu üzerinde yer alan başarılı kentsel mekanların kalitesini ortaya koymaktır. Bu araştırmanın temel amacı İpek Yolu kentlerinde başarılı kentsel kamusal alanlar yaratabilmek için en doğru yaklaşımı ya da metodu ortaya çıkarmaktır. Bu yolla, iki temel hedef ortaya konmuştur. Bunlardan birincisi İran’da İpek Yolu üzerindeki yerleşimlerde kentsle kamusal alanların genel özelliklerinin belirlenmesi; ve diğeri, İpek Yolu kentlerindeki kentsel mekanların başarılı olabilmesi için çeşitli yer-tasarımı yaklaşımlarının ortaya konulmasıdır. Bu amaçlar doğrultusunda iki bağımız ancak ilişkili araştırma sorusu belirlenmiştir: Yer-tasarımı için stratejiler neler olmalıdır? Yer-tasarımı, İran’daki İpek Yolu kentlerinde yer alan kentsel kamusal alanların kalitesini nasıl artırabilir? Bu araştırma, yer ve yer-tasarımı konularındaki kuramsal tarama ile başlamıştır. Konuyla ilgili temel tanımlar ve alanlar açıklanmış ve anlaşılmıştır. Bağlantılı olarak, yer-tasarımı ile ilgili temel kriterler incelenmiş ve analiz metodolojisi ortaya konmuştur. Bu inceleme sonucunda bir yeri başarılı kılan özelliklerin hiyerarşisi ve ağırlığı ortaya çıkarılmıştır. Alan çalışması, İran’daki İpek Yolu kentlerinin ve yerleşimleri ile ilgili doküman araştırması ile başlatılmıştır. Ayrıntılı doküman çalışması sonucunda İpek Yolu ve üzerindeki yerleşimler tanıtılmıştır. Bu bölüm, İpek Yolu üzerinde yer alan her kentin coğrafi konumu, iklimsel özellikler, ekonomik yapısı ve nüfusu ile ilgili bilgileri kapsamaktadır. Alan çalışmasının ikinci bölümü, İpek Yolu kentlerinşde yer alan kentsel mekanların analizini kapsamaktadır. Bu araştırmada, toplamda 17 kentte yer alan 650 yer listelenmiştir. Araştırmayı sınırlandırmak üzere, yerlerin seçimi için bir eleme metodu kullanılmış ve sonuçta üç kentten oniki yer seçilmiştir. Bu metotda, öncelikle kentlein dışında kalan yerler elenmiştir. Daha sonra, kentlerin ana formu dışında kalan yerler elenmiş; ve sonunda tarihi kentsel merkezde yer alan yerler seçilmiştir. Analiz kısmında, elde kalan 12 yer, kuramsal inceleme sonucunda ortaya konan değerlendirme kriterlerine bağlı kalınarak araştırılmıştır. Analiz, yer-tasarımı değerlendirmelerinin, İran’daki İpek Yolu üzerindeki kentlerde yer alan yerlerin kalitesi üzerine yoğunlaşmıştır. Bu tezde yer alan araştırmanın sonuçlarına göre, sokak yaşamı ve yaya aktiviteleri, İpek Yolu kentlerinde yer alan mekanlarının başarısı üzerinde en etkili faktörlerdir. Araştırma sonuçları ayrıca, ticaret gibi fonkisyonların da yerlerin başarısında önemli rol oynadığını; yer olarak seçilmiş olan pazar alanlarının, cami mekanları, kent girişleri ve saraylar içinde en başarılı yerler olarak ortaya çıktığını göstermiştir.Arştırmanın bir digger bulgusu da, başarılı yer-tasarımında kentlerin ölçeğinin daha az önemli olduğudur.
Doctor of Philosophy in Architecture. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2013. Supervisor: Prof. Dr. Şebnem Önal Hoşkara.
Keywords: Architecture; City planning - Social aspects - Iran; City Planning - Community Development; Silk Road, Place, Placemaking, Iran, SAW Methodology